Export and Import in the Republic of Moldova Ensured by the Negotiations of International Agreements in the Last 10 Years (Acta Universitatis Danubius. Œconomica, 2024)
Correlation between import and export is essential for a country's economic development and stability. Adequate management of these processes can contribute to economic growth, resource diversification, strengthening international relations and improving the quality of life for citizens. The author intends to present in this article the evolution and particularities of import and export in the Republic of Moldova in the last 10 years. During this period our country faced several events, difficult economic periods, crises, situations of force majeure, etc. But by negotiating international agreements with the European Union, international organizations, other independent states, it was possible to register a positive evolution of exports and imports. As a result, the author proposes the correlation between import and export as an essential part for economic development and stability of the Republic of Moldova.